2016
DOI: 10.1002/lt.24470
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric liver transplantation: Personal perspectives on historical achievements and future challenges

Abstract: This review presents the author's personal perspective and contributions to the first steps, the development, the current status, and the remaining issues of pediatric liver transplantation (LT). Innumerable children around the world who have undergone LT have reached adulthood. The techniques have reached maturity. As shown by my own group's experience, grafts donated by living donors might provide the best short-term and longterm results. Debate persists about the optimal immunosuppression (IS), although the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 64 publications
1
34
0
1
Order By: Relevance
“…It was close to a 98% actual patient survival over a 7‐year period—and with a minimum follow‐up of 2 years afterward for each graft. These results compare well with other series that have been published recently or even earlier . More interestingly, these results have suggested that the vast majority of surviving grafts have an excellent function at the very long‐term point, with fully normal liver tests in 78.7% of the patients.…”
Section: Discussionsupporting
confidence: 90%
“…It was close to a 98% actual patient survival over a 7‐year period—and with a minimum follow‐up of 2 years afterward for each graft. These results compare well with other series that have been published recently or even earlier . More interestingly, these results have suggested that the vast majority of surviving grafts have an excellent function at the very long‐term point, with fully normal liver tests in 78.7% of the patients.…”
Section: Discussionsupporting
confidence: 90%
“…Currently, immunosuppression in pediatric liver transplantation consists of multidrug therapy including induction therapy, low‐dose tacrolimus, steroids, sirolimus, and/or mycophenolate mofetil . The aim of the treatment is to avoid rejection but also to minimize renal dysfunction, PTLD, infection, hypertension, and hyperlipidemia .…”
Section: Introductionmentioning
confidence: 99%
“…Liver transplantation has become a standard procedure for children with end-stage liver disease [2]. The most common clinical indications for liver transplant in pediatric patients are cholestatic liver disease, which accounts for almost half of the patients; metabolic and genetic disorders; fulminant liver failure; and malignancies [3][4][5].…”
Section: Introductionmentioning
confidence: 99%